ACe-C-PPy composite material and preparation method and application thereof

By using ACe@C@PPy composite material in the lithium-sulfur battery separator, the problems of low sulfur utilization, low Coulomb efficiency and short cycle life of lithium-sulfur batteries are solved, and the effects of high conductivity, high capacity and long cycle stability are achieved.

CN119890609APending Publication Date: 2025-04-25GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510071091.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Lithium sulfur batteries have hindered their practical application due to their low sulfur utilization rate, low Coulomb efficiency, poor cycle life and the shuttle effect caused by the dissolution and diffusion of soluble polysulfide lithium intermediates.

Method used

ACe@C@PPy composite material is used as the separator material for lithium sulfur batteries. After high-temperature carbonization of A-MOF material, it is composited with Ce to form ACe@C material, and the PPy layer is wrapped on its surface to form an egg yolk shell structure, enhancing conductivity and adsorption ability.

Benefits of technology

The rapid conversion of Li2Sx is achieved, the shuttle effect is alleviated, and the conductivity, capacity, Coulomb efficiency and cycle stability of lithium-sulfur batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890609A_ABST
    Figure CN119890609A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium-sulfur battery diaphragm materials, and particularly relates to an ACe-C-PPy composite material as well as a preparation method and application thereof. An A-MOF material is used as a main body, an A-C material is obtained through high-temperature carbonization, A is selected from Fe or Co, then the A-C material and Ce are compounded to generate an ACe-C material, the ACe-C material is a three-dimensional A and Ce co-doped carbon nano frame derived from ZIF, and then the surface of the ACe-C material is coated with a layer of polypyrrole through an ice-bath stirring method to prepare the ACe-C-PPy composite material. The porous structure of the ACe (at) C (at) PPy composite material is beneficial to Li < + > transmission and electrolyte diffusion, the synergistic effect of A-Ce diatom doping promotes polysulfide conversion, the coated polypyrrole enhances the conductivity, and the interface material has a lithium-loving characteristic, can effectively inhibit the growth of lithium dendrites, and is used for modifying a high-performance lithium-sulfur battery diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-sulfur battery separator materials, and in particular relates to an ACe@C@PPy composite material and a preparation method and application thereof. Background Art

[0002] Due to the burning of fossil fuels, global environmental problems are becoming more and more serious. People are committed to seeking clean energy to improve and solve the current situation. How to better store and utilize clean energy has become a key issue. Lithium-sulfur (Li-S) batteries have a capacity of 2600Whkg -1 High quality energy density and over 1600mAhg -1 Theoretical specific capacity of sulfur cathode materials is high, and sulfur cathode materials have the advantages of abundant reserves, low cost and non-toxicity, making them a new star in the energy storage industry. However, lithium-sulfur batteries also have several key problems, such as low sulfur utilization, low Coulombic efficiency (CE), poor cycle life and soluble lithium polysulfide (Li2S x )The shuttle effect caused by the dissolution and diffusion of intermediates hinders its practical application.

[0003] To overcome the above challenges, researchers have conducted extensive studies on different conductive carbons, polymers, additives, adhesives, electrolytes, and engineered cathode materials. Composite modified separators have also been found to be one of the effective methods to alleviate the dissolution of lithium polysulfide intermediates (LIPSs) to improve electrochemical performance. Various conductive materials have been used as coatings and introduced between the cathode and the separator to delay the shuttling of dissolved LIPSs by physical blocking or chemical adsorption, and can also inhibit the volume expansion of sulfur. For example, conductive metal oxides, carbon materials, and conductive polymers have all been used in the modification of separators for lithium-sulfur batteries (LSBs).

[0004] In the existing technology, only one material is often used or only one function is achieved, which cannot comprehensively improve the performance of the battery. For example, carbon materials can improve conductivity, but cannot achieve the adsorption and catalytic effect of polysulfides on the diaphragm; pure oxides generally have poor conductivity and large polarization effect; polymers only provide stability and physical adsorption. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides an ACe@C@PPy composite material and its preparation method and application. The present invention uses A-MOF material as the main body, obtains A@C material by high-temperature carbonization, and then composites the A@C material with Ce to generate ACe@C material, which is a three-dimensional A and Ce co-doped carbon nanoframe derived from ZIF. Then, a layer of PPy is wrapped on the surface of the ACe@C material by ice bath stirring to form a spherical structure of egg yolk shell to obtain ACe@C@PPy composite material. The porous structure of ACe@C@PPy composite material itself is conducive to Li + The synergistic effect of A-Ce diatomic doping promotes polysulfide conversion, and the encapsulated polypyrrole enhances conductivity. Its interface material has lithium-philic properties, which can effectively inhibit the growth of lithium dendrites and can be used to modify high-performance lithium-sulfur battery separators. x conversion, alleviating the shuttle effect, and utilizing the catalytic-adsorption synergistic effect of A-Ce bimetallic, showing high conductivity, high capacity, high Coulombic efficiency and long cycle stability.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing an ACe@C@PPy composite material comprises the following steps:

[0008] In an inert atmosphere, the A-MOF material is carbonized at high temperature, wherein A is selected from Fe or Co, to obtain an A@C material.

[0009] The A@C material and soluble cerium salt are mixed in anhydrous ethanol, heated, and the A@C material and Ce are compounded. The solvent anhydrous ethanol is separated to obtain ACe@C material. ACe@C material cannot be obtained with other solvents.

[0010] Pyrrole aqueous solution, Fe 3+ The solution and the suspension of ACe@C material were mixed to form Fe 3+ As a catalyst for catalytic polymerization, after pyrrole is polymerized, polypyrrole coats the ACe@C material to obtain an ACe@C@PPy composite material.

[0011] Preferably, the high temperature carbonization temperature is 915-1000°C, and the carbonization time is 2-3h. If the temperature is lower than 907°C, Zn + It cannot vaporize, the temperature is too high and the temperature of the pipe furnace cannot be met.

[0012] Preferably, the mass ratio of the A@C material to the soluble cerium salt is 1:3-4, and the mass concentration of the total amount of the A@C material and Ce(NO3)3·6H2O in anhydrous ethanol is 8-10 g / mL.

[0013] Preferably, the heating conditions are: stirring at 75-85° C. for 6-8 hours and a stirring rate of 250-300 r / min.

[0014] Preferably, the mass ratio of ACe@C material to pyrrole is 4:1-1.5, and the mass ratio of pyrrole to Fe 3+ The molar ratio of ACe@C material to pyrrole is 1:3 to 4. Too large a ratio of ACe@C material to pyrrole will result in incomplete coating, while too small a ratio will result in an overly thick coating layer, which is not conducive to ion diffusion.

[0015] Preferably, the suspension of ACe@C material is prepared according to the following steps: 200-210 mg of ACe@C material is ultrasonically dispersed in 15-17 mL of polyvinyl pyrrolidone aqueous solution, and the concentration of the polyvinyl pyrrolidone aqueous solution is 0.4 mol / L.

[0016] Preferably, 0.9-1 g of FeCl3·6H2O is dissolved in 10-12 mL of deionized water to prepare Fe 3+ Solution.

[0017] Preferably, the polymerization operation is: first add the pyrrole solution to the suspension of ACe@C material and stir for 10 to 12 minutes, then add Fe 3+ The solution was stirred at 0 °C in the dark for 12-13 h.

[0018] The present invention also protects the ACe@C@PPy composite material prepared by the above preparation method.

[0019] The present invention also protects the use of the above ACe@C@PPy composite material in the preparation of modified lithium-sulfur battery separator materials.

[0020] Preferably, the modified lithium-sulfur battery separator material is prepared according to the following steps: grind and mix the ACe@C@PPy composite material, the conductive agent and the binder, add N-methylpyrrolidone, and then filter onto a Celgard2400PP separator and dry to obtain a modified lithium-sulfur battery separator material, which is recorded as ACe@C@PPy / PP separator.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention uses A-MOF (A is selected from Fe or Co) as the main material, obtains A@C material by high-temperature carbonization, obtains nitrogen-doped carbon after carbonization of MOF in A@C material, and obtains ACe@C material after Ce is compounded on A@C material. This material is a carbon material doped with heteroatoms containing uniformly embedded bimetallic nanoparticles, which exhibits uniqueness that cannot be obtained by single metal-doped carbon composite materials. It is not only Li2S x Provides high chemical affinity and fast Li2Sx redox kinetics; moreover, the electron transfer between different metals can tune the electron density distribution between them, giving bimetallic catalysts tunable adsorption and catalytic properties.

[0023] A layer of PPy was coated on the surface of ACe@C material by ice bath stirring to form a spherical structure of egg yolk shell, and ACe@C@PPy composite material was obtained. PPy has good conductivity and stable physical and chemical properties, and is an excellent LIPSs fixative. The coated PPy can not only enhance the conductivity of ACe@C@PPy composite material, but also the PPy material at its interface has lithium affinity, which can effectively reduce the deposition overpotential of lithium and ensure Li + The ACe@C@PPy composite material can be used as a separator in lithium-sulfur batteries to achieve Li2S x Conversion and mitigation of Li2S x To solve the shuttle effect problem and improve the electrochemical performance of lithium-sulfur batteries.

[0024] The A-MOF material is carbonized at high temperature to obtain a honeycomb 3D porous carbon nanoframe loaded with A, namely A@C material. The porous carbon nanoframe can accommodate the volume expansion of S, provide good conductivity, fast electrolyte penetration and mass transfer, and overcome the problem that non-polar porous carbon materials cannot effectively adsorb polar Li2S x technical defects.

[0025] After Ce is compounded on A@C material, ACe@C material is obtained, which is an embedded bimetallic carbide with good catalytic and adsorption synergy. The large specific surface area provides a large number of electrochemical active sites, which can quickly limit / adsorb Li2S x , and effectively realize Li2S x Acceleration and redox kinetics.

[0026] 2. The present invention uses ACe@C@PPy composite material as the separator material of Li-S battery, which has the following advantages: (i) The 3D porous carbon nanoframe accommodates the volume expansion of S, provides good conductivity, rapid electrolyte penetration and mass transfer. (ii) The well-embedded bimetallic carbides have a synergistic effect and sufficient chemical adsorption. Its electroactive sites can quickly adsorb LIPSs and effectively accelerate the redox kinetics of LIPSs. (iii) The encapsulated PPy can not only enhance the conductivity of the material, but its interface material also has lithium-philic properties, which can effectively reduce the deposition overpotential of lithium and ensure Li + The uniform transport of lithium ions and the suppression of lithium dendrites can be achieved, so the obtained ACe@C@PPy composite material has high capacity, high Coulombic efficiency and long cycle stability. It is a composite material with multiple functions and can be used for the modification and improvement of existing separators. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Scanning electron microscope (SEM) images of the cross section of the FeCe@C@PPy composite material of Example 1 of the present invention at different magnifications.

[0028] Figure 2 This is the X-ray diffraction (XRD) diagram of the FeCe@C@PPy composite material of Example 1 of the present invention.

[0029] Figure 3 This is a scanning electron microscope (SEM) image of the cross section of the CoCe@C@PPy composite material of Example 2 of the present invention.

[0030] Figure 4 This is a diagram showing the adsorption effect of polysulfide on the Fe@C material, FeCe@C material and FeCe@C@PPy composite material of Example 1 of the present invention.

[0031] Figure 5 This is a graph of the electrochemical cycling performance of the FeCe@C@PPy composite material of Example 1 and the CoCe@C@PPy composite material of Example 2 at 0.2C. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0033] Taking into account that the existing technology cannot obtain a diaphragm material that comprehensively improves battery performance, the present invention provides an ACe@C@PPy (A is selected from Fe or Co) composite material. The ACe@C@PPy composite material has high conductivity, high capacity, high Coulomb efficiency and long cycle stability, and the A-Ce bimetal has a catalytic-adsorption synergistic effect.

[0034] The present invention provides a method for preparing an ACe@C@PPy composite material, comprising the following steps:

[0035] Step 1: Preparation of ACe@C material: Carbonize the A-Zn MOF material at high temperature and evaporate Zn + A-MOF material is obtained; it should be noted that the present invention does not limit the specific method of specific processing, as long as A-MOF can be obtained. Preferably, the present invention adopts steps S1 to S3 to prepare A-MOF:

[0036] S1. Mix A(NO3)2·6H2O (A is selected from Fe or Co), Zn(NO3)2·6H2O and terephthalic acid in DMF, anhydrous ethanol and ultrapure water; wherein the molar ratio of A(NO3)2·6H2O, Zn(NO3)2·6H2O and terephthalic acid is 1:1:4, the volume ratio of DMF, anhydrous ethanol and ultrapure water is 14:1:1, and the volume ratio of terephthalic acid to ultrapure water is 8mmol:5mL; in the present invention, the preferred mixing method is stirring, and the stirring rate is 200r / min, and the time is 2h.

[0037] S2. After stirring, place in a 100 mL Teflon-lined reactor and keep at 125° C. for 4 h. After the reaction is completed, collect the precipitate and wash and dry it in time to obtain A-Zn MOF material; wherein, after the reaction is completed, collect the precipitate by filtration, and wash it repeatedly with ultrapure water and ethanol at a speed of 8000 r / min in a centrifuge for 3 times to remove impurities inside, and finally dry it in a vacuum drying oven at 60° C. for 12 h to obtain A-Zn MOF material.

[0038] S3, high temperature carbonization of A-Zn MOF material to remove Zn + A-MOF material was obtained; in a nitrogen-filled tube furnace, the A-ZnMOF material was carbonized at 915-1000°C for 2-3h with a heating rate of 2°C / min, because Zn + The boiling point is 907℃, and the removal of Zn + It can form the material into a honeycomb structure, providing a large space for sulfur storage.

[0039] Step 2: Place the A-MOF material and Ce(NO3)3·6H2O in an organic solvent and stir at 75-85°C for 6-8h to generate ACe@C. Disperse and mix A@C and Ce(NO3)3·6H2O with an organic solvent in a ratio of 1g:3-4g:500mL, stir the reaction, collect the precipitate by centrifugation, and prepare ACe@C material after drying.

[0040] Step 3, preparation of ACe@C@PPy composite material: ultrasonically disperse ACe@C material in 0.4 mol / L PVP aqueous solution for 1 min, and stir the resulting turbid suspension for 30 min to obtain a suspension of ACe@C material. 3+ Solution and pyrrole solution, first add pyrrole solution to the suspension of ACe@C material and stir for 10 min, then add Fe 3+The solution was stirred at 0 °C in the dark for 12-13 h. After the reaction, the precipitate was collected by centrifugation and then repeatedly washed with deionized water and ethanol to remove the pyrrole monomer and salt residues in the product. Finally, the precipitate was vacuum dried at 60 °C for 12 h to provide the final dried ACe@C@PPy composite material.

[0041] Step 4, preparation of ACe@C@PPy composite material modified diaphragm: grind and mix the ACe@C@PPy composite material with conductive carbon black and PVDF in a mass ratio of 7:2:1, add NMP for ultrasonic dispersion for 10 minutes, then filter onto Celgard 2400PP diaphragm, and vacuum dry for 12 hours to obtain ACe@C@PPy@PP diaphragm.

[0042] The technical solution of the present invention is further explained by using embodiments below, which are specifically as follows:

[0043] Example 1

[0044] A method for preparing a FeCe@C@PPy diaphragm composite material comprises the following steps:

[0045] Step 1: Preparation of FeCe@C material:

[0046] S1. Preparation of Fe-Zn MOF material by solvothermal method: 0.808g of Fe(NO3)3·9H2O, 0.595g of Zn(NO3)2·6H2O (the molar ratio of Fe:Zn is 1:1, and the purpose of establishing the two atomic ratios is to enable Fe-Zn to form a MOF material with a face-centered cubic structure) and 0.665g of terephthalic acid are added to a mixed solvent, stirred for 0.5h, placed in a Teflon-lined reactor with a volume of 100mL, and kept at 125°C for 4h. After the reaction is completed, the precipitate is collected by filtration, and washed repeatedly with ultrapure water and ethanol by centrifugation for 3 times, and finally dried in a vacuum drying oven at 80°C for 12h to obtain Fe-ZnMOF material.

[0047] The mixed solvent consists of 35 mL of N,N'-dimethylformamide, 2.5 mL of anhydrous ethanol and 2.5 mL of ultrapure water.

[0048] S2. In a tubular furnace filled with nitrogen, the Fe-Zn MOF material was carbonized at 920 °C for 3 h to obtain the Fe@C material.

[0049] S3. Disperse 0.12 g of Fe@C material in a Teflon-lined stainless steel autoclave filled with 60 mL of ethanol to obtain a suspension, then add 0.36 g of Ce(NO3)3·6H2O to the suspension, stir evenly and heat at 80°C for 6 h to prepare a hollow FeCe@C precursor, wash the FeCe@C precursor three times with water and dry it under vacuum at 60°C overnight to obtain the FeCe@C material.

[0050] Step 2: Preparation of FeCe@C@PPy composite material:

[0051] 200 mg of FeCe@C material was dispersed in 15 mL of 0.4 mol / L PVP aqueous solution by ultrasonication for 1 min, and the resulting turbid suspension was stirred for 30 min to obtain a suspension of FeCe@C material. 3+ solution (0.9 g of FeCl3·6H2O and 10 mL of deionized water) and pyrrole solution (pyrrole monomer and 15 mL of deionized water), where the mass ratio of FeCe@C material to pyrrole is 4:1, and the mass ratio of pyrrole to FeCe@C material is 4:1. 3+ The molar ratio of FeCe@C was 1:3. The pyrrole solution was first added to the suspension of FeCe@C material and stirred for 10 min, and then Fe 3+ The solution was stirred at 0 °C in the dark for 12 h. After the reaction, the precipitate was collected by centrifugation and then repeatedly washed with deionized water and ethanol to remove the pyrrole monomer and salt residues in the product. Finally, the precipitate was vacuum dried at 60 °C for 12 h to provide the final dried FeCe@C@PPy composite material.

[0052] The preparation of the FeCe@C@PPy composite material modified diaphragm includes the following steps:

[0053] The FeCe@C@PPy composite material was ground and mixed with conductive carbon black and PVDF (mass ratio of 7:2:1), and then NMP was added for ultrasonic dispersion for 10 minutes. It was then filtered onto a Celgard 2400PP membrane and vacuum dried for 12 hours to obtain a FeCe@C@PPy / PP membrane.

[0054] Example 2

[0055] A method for preparing a CoCe@C@PPy diaphragm composite material comprises the following steps:

[0056] Step 1: Preparation of CoCe@C material:

[0057] S1. Preparation of Co-Zn MOF material by solvothermal method: 0.582g of Co(NO3)2·6H2O, 0.595g of Zn(NO3)2·6H2O (Co:Zn=1:1) and 0.665g of terephthalic acid were added to the mixed solvent, stirred for 0.5h, placed in a Teflon-lined reactor with a volume of 100mL, and kept at 125°C for 4h. After the reaction was completed, the precipitate was collected by filtration, and washed repeatedly with ultrapure water and ethanol by centrifugation for 3 times, and finally dried in a vacuum drying oven at 80°C for 12h to obtain Co-Zn MOF material. (The purpose of establishing the two atomic ratios is to enable Co-Zn to form a MOF material with a face-centered cubic structure).

[0058] The mixed solvent consists of N,N'-dimethylformamide (35 mL), anhydrous ethanol (2.5 mL) and ultrapure water (2.5 mL).

[0059] S2. In a tubular furnace filled with nitrogen, the Co-Zn MOF material was carbonized at 920 °C for 3 h to obtain the Co@C material.

[0060] S3. Disperse 0.12 g of Co@C material in a Teflon-lined stainless steel autoclave filled with 60 mL of ethanol to obtain a suspension, then add 0.36 g of Ce(NO3)3.6H2O to the suspension, stir evenly and heat at 80°C for 6 h to prepare a hollow CoCe@C precursor, wash the yellowish-brown CoCe@C precursor three times with water and dry it under vacuum at 60°C overnight to obtain the CoCe@C material.

[0061] Step 2: Preparation of CoCe@C@PPy composite material:

[0062] 200 mg of CoCe@C material was dispersed in 15 mL of 0.4 mol / L PVP aqueous solution by ultrasonication for 1 min, and the resulting turbid suspension was stirred for 30 min to obtain a suspension of CoCe@C material. 3+ solution (0.9 g of FeCl3·6H2O and 10 mL of deionized water) and pyrrole solution (pyrrole monomer and 15 mL of deionized water), where the mass ratio of CoCe@C material to pyrrole is 4:1, and the mass ratio of pyrrole to Fe 3+ The molar ratio of FeCe@C was 1:3. The pyrrole solution was first added to the suspension of FeCe@C material and stirred for 10 min, and then Fe 3+ The solution was stirred at 0 °C in the dark for 12 h. After the reaction, the precipitate was collected by centrifugation and then repeatedly washed with deionized water and ethanol to remove the pyrrole monomer and salt residues in the product. Finally, the precipitate was vacuum dried at 60 °C for 12 h to provide the final dried CoCe@C@PPy composite material.

[0063] The preparation of the CoCe@C@PPy composite material modified diaphragm includes the following steps:

[0064] The CoCe@C@PPy composite material was ground and mixed with conductive carbon black and PVDF (mass ratio of 7:2:1), and NMP was added for ultrasonic dispersion for 10 minutes. It was then filtered onto a Celgard 2400PP membrane and vacuum dried for 12 hours to obtain a CoCe@C@PPy / PP membrane.

[0065] The obtained CoCe@C@PPy / PP separator material can be used as separator material for lithium-sulfur batteries.

[0066] Example 3

[0067] A method for preparing a FeCe@C@PPy diaphragm composite material comprises the following steps:

[0068] Step 1: Preparation of FeCe@C material:

[0069] S1. Preparation of Fe-Zn MOF material by solvothermal method: 0.808 g of Fe(NO3)3·9H2O, 0.595 g of Zn(NO3)2·6H2O (the molar ratio of Fe:Zn is 1:1, and the purpose of establishing the two atomic ratios is to make A-Zn determine to form a MOF material with a face-centered cubic structure) and 0.665 g of terephthalic acid are added to a mixed solvent, stirred for 0.5 h, placed in a Teflon-lined reactor with a volume of 100 mL, and kept at 125°C for 4 h. After the reaction is completed, the precipitate is collected by filtration, and washed repeatedly with ultrapure water and ethanol by centrifugation for 3 times, and finally dried in a vacuum drying oven at 80°C for 12 h to obtain Fe-ZnMOF material.

[0070] The mixed solvent consists of 35 mL of N,N'-dimethylformamide, 2.5 mL of anhydrous ethanol and 2.5 mL of ultrapure water.

[0071] S2. In a tubular furnace filled with nitrogen, the Fe-Zn MOF material was carbonized at 1000°C for 2 h to obtain the Fe@C material.

[0072] S3. Disperse 0.12 g of Fe@C material in a Teflon-lined stainless steel autoclave filled with 60 mL of ethanol to obtain a suspension, then add 0.48 g of Ce(NO3)3·6H2O to the suspension, stir evenly and heat at 75°C for 8 h to prepare a hollow FeCe@C precursor, wash the FeCe@C precursor three times with water and dry it under vacuum at 60°C overnight to obtain the FeCe@C material.

[0073] Step 2: Preparation of FeCe@C@PPy composite material:

[0074] 200 mg of FeCe@C material was dispersed in 15 mL of 0.4 mol / L PVP aqueous solution by ultrasonication for 1 min, and the resulting turbid suspension was stirred for 30 min to obtain a suspension of FeCe@C material. 3+ solution (0.9 g of FeCl3·6H2O and 10 mL of deionized water) and pyrrole solution (pyrrole monomer and 20 mL of deionized water), where the mass ratio of FeCe@C material: pyrrole is 4:1.5, and the mass ratio of pyrrole: Fe 3+ The molar ratio of FeCe@C was 1:4. The pyrrole solution was first added to the suspension of FeCe@C material and stirred for 10 min, and then Fe 3+ The solution was stirred at 0 °C in the dark for 13 h. After the reaction, the precipitate was collected by centrifugation and then repeatedly washed with deionized water and ethanol to remove the pyrrole monomer and salt residues in the product. Finally, the precipitate was vacuum dried at 60 °C for 12 h to provide the final dried FeCe@C@PPy composite material.

[0075] Example 4

[0076] A method for preparing a CoCe@C@PPy diaphragm composite material comprises the following steps:

[0077] Step 1: Preparation of CoCe@C material:

[0078] S1. Preparation of Co-Zn MOF material by solvothermal method: 0.582 g of Co(NO3)2·6H2O, 0.595 g of Zn(NO3)2·6H2O (the molar ratio of Co:Zn is 1:1, and the purpose of establishing the two atomic ratios is to ensure that Co-Zn can form a MOF material with a face-centered cubic structure) and 0.665 g of terephthalic acid are added to a mixed solvent, stirred for 0.5 h, placed in a Teflon-lined reactor with a volume of 100 mL, and kept at 125°C for 4 h. After the reaction is completed, the precipitate is collected by filtration, and washed repeatedly with ultrapure water and ethanol by centrifugation for 3 times, and finally dried in a vacuum drying oven at 80°C for 12 h to obtain Co-ZnMOF material.

[0079] The mixed solvent consists of N,N'-dimethylformamide (35 mL), anhydrous ethanol (2.5 mL) and ultrapure water (2.5 mL).

[0080] S2. In a tubular furnace filled with nitrogen, the Co-ZnMOF material was carbonized at 915°C for 3 h to obtain the Co@C material.

[0081] S3. Disperse 0.12 g of Co@C material in a Teflon-lined stainless steel autoclave filled with 60 mL of ethanol to obtain a suspension, then add 0.40 of Ce(NO3)3.6H2O to the suspension, stir evenly and heat at 85°C for 7 h to prepare a hollow CoCe@C precursor, wash the yellowish-brown CoCe@C precursor three times with water and dry it under vacuum at 60°C overnight to obtain the CoCe@C material.

[0082] Step 2: Preparation of CoCe@C@PPy composite material:

[0083] 200 mg of CoCe@C material was dispersed in 15 mL of 0.4 mol / L PVP aqueous solution by ultrasonication for 1 min, and the resulting turbid suspension was stirred for 30 min to obtain a suspension of CoCe@C material. 3+ solution (0.9 g of FeCl3·6H2O and 10 mL of deionized water) and pyrrole solution (pyrrole monomer and 20 mL of deionized water), where the mass ratio of CoCe@C material: pyrrole is 4:1.5, and the mass ratio of pyrrole: Fe 3+ The molar ratio of FeCe@C was 1:4. The pyrrole solution was first added to the suspension of FeCe@C material and stirred for 10 min, and then Fe 3+ The solution was stirred at 0 °C in the dark for 12 h. After the reaction, the precipitate was collected by centrifugation and then repeatedly washed with deionized water and ethanol to remove the pyrrole monomer and salt residues in the product. Finally, the precipitate was vacuum dried at 60 °C for 12 h to provide the final dried CoCe@C@PPy composite material.

[0084] Examples 1 to 4 of the present invention all produce ACe@C@PPy composite materials with high conductivity, high capacity, high Coulomb efficiency and long cycle stability. The following study is conducted by taking the FeCe@C@PPy composite material of Example 1 and the CoCe@C@PPy composite material of Example 2 as examples. The specific research methods and results are as follows:

[0085] The FeCe@C@PPy composite material obtained in Example 1 can be used as a separator material for lithium-sulfur batteries. The SEM image of the FeCe@C@PPy composite material is shown in FIG. Figure 1 As shown in (a) and (b), it is obvious that PPy is uniformly coated on the surface of the honeycomb FeCe@C, which further illustrates that the conductivity of the FeCe@C@PPy composite material has been greatly improved. The formation of Li-N bonds between PPy and LIPSs is also beneficial to the adsorption of LIPSs. By forming a core-shell structure and Li-N bonds, LIPSs are inhibited from entering the electrolyte from both physical barriers and chemical adsorption, thereby inhibiting the dissolution of LIPSs and reducing the loss of active substances, thereby improving the electrochemical reversibility and cycle stability.

[0086] Figure 2 This is the XRD test diagram of the FeCe@C@PPy composite material of Example 1. The XRD of the wrapped FeCe@C@PPy composite material is no different from that of the FeCe@C material, which proves that after wrapping PPy, PPy only stays on the surface of the material and does not change the lattice structure of the FeCe@C material. It also indirectly shows that the conductivity of the surface of the FeCe@C@PPy composite material has been greatly improved.

[0087] Figure 3 This is the SEM image of the CoCe@C@PPy composite material of Example 2. It can be seen that PPy is uniformly coated on the surface of the honeycomb CoCe@C material, which further illustrates that the conductivity of the CoCe@C@PPy composite material itself has been greatly improved.

[0088] Figure 4 This is the adsorption diagram of polysulfide of FeCe@C@PPy composite material in Example 1. In order to verify the adsorption capacity of different materials for polysulfide, we used static adsorption experiment to verify. Fe@C material, FeCe@C material and FeCe@C@PPy composite material of equal mass were added to 5mmol / L Li2S6 solution, and then adsorption experiment was carried out. After 1h, it was found that compared with the original brick red Li2S6 solution, the color of Li2S6 solution changed to varying degrees after adding Fe@C material, FeCe@C material and FeCe@C@PPy composite material. Compared with Fe@C material and FeCe@C material, the solution with FeCe@C@PPy composite material added is transparent and nearly colorless, which proves that FeCe@C@PPy composite material has super strong adsorption effect on Li2S6.

[0089] Figure 5 The cycle performance diagram of a lithium-sulfur battery assembled with the FeCe@C@PPy composite modified diaphragm of Example 1 and the CoCe@C@PPy composite modified diaphragm of Example 2 at 0.2C is shown in the figure. The lithium-sulfur battery assembly method is:

[0090] Preparation of positive electrode sheet: Active material, conductive agent carbon black and binder PVDF were mixed evenly in a mass ratio of 7:2:1, and after grinding for 30 minutes, N-methylpyrrolidone was added and grinding was continued to form an oily slurry, wherein the active material was composed of carbon and sulfur in a mass ratio of 3:7. The aluminum foil was laid flat and wiped clean with alcohol, and the oily slurry was transferred to the surface of the aluminum foil, and then scraped evenly with a 20μm metal scraper, and then placed in a 60℃ oven to dry overnight, and the aluminum foil with the oily slurry was cut into circular electrode sheets with a diameter of 16mm using a sheet press.

[0091] In a glove box filled with argon, a circular electrode sheet was used as the positive electrode, a lithium sheet was used as the negative electrode, and 1 mol / L LiTFSI (the volume ratio of DME:DOL was 1:1, containing 1% LiNO3) was used as the electrolyte. In addition, the ACe@C@PPy@PP membrane was used as the separator, and the battery was assembled using a CR-2025 battery shell. After completion, the battery performance test was carried out after standing at 25°C for 10 hours. The results showed that the initial capacity of the battery was 1585mAh·g -1 , the discharge specific capacity has been greatly improved.

[0092] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an ACe@C@PPy composite material, characterized in that: The following steps are involved: In an inert atmosphere, the A-MOF material is carbonized at high temperature, wherein A is selected from Fe or Co, to obtain an A@C material; The A@C material and the soluble cerium salt are mixed in anhydrous ethanol, heated, and the A@C material and Ce are compounded, and the solvent anhydrous ethanol is separated to obtain the ACe@C material; Pyrrole aqueous solution, Fe 3+ The solution and the suspension of ACe@C material are mixed, and after pyrrole is polymerized, polypyrrole coats the ACe@C material to obtain an ACe@C@PPy composite material.

2. The method for preparing an ACe@C@PPy composite material according to claim 1, characterized in that: The temperature of high temperature carbonization is 915-1000°C, and the carbonization time is 2-3h.

3. The method for preparing an ACe@C@PPy composite material according to claim 1, characterized in that: The mass ratio of A@C material to soluble cerium salt is 1:3-4.

4. The method for preparing an ACe@C@PPy composite material according to claim 1, characterized in that: The heating conditions are: stirring at 75-85°C for 6-8h.

5. The method for preparing an ACe@C@PPy composite material according to claim 1, characterized in that: The mass ratio of ACe@C material to pyrrole is 4:1-1.

5. 3+ The molar ratio is 1:3~4.

6. The method for preparing an ACe@C@PPy composite material according to claim 1, characterized in that: The suspension of ACe@C material was prepared according to the following steps: the ACe@C material was ultrasonically dispersed in a polyvinyl pyrrolidone aqueous solution.

7. A method for preparing an ACe@C@PPy composite material according to claim 1, characterized in that: The polymerization conditions are: stirring at 0°C in the dark for 12 to 13 hours.

8. An ACe@C@PPy composite material obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the ACe@C@PPy composite material according to claim 8 in preparing a modified lithium-sulfur battery separator material.

10. The use according to claim 9, characterized in that: The modified lithium-sulfur battery separator material is prepared according to the following steps: The ACe@C@PPy composite material, the conductive agent and the binder were ground and mixed, and N-methylpyrrolidone was added. The mixture was then filtered onto a Celgard 2400PP separator and dried to obtain a modified lithium-sulfur battery separator material.